Up-regulated microRNA-33b inhibits epithelial–mesenchymal transition in gallbladder cancer through down-regulating CROCC. Issue 1 (10th January 2020) - Xu, Guohui; Wei, Xiaoyong; Tu, Qiang; Zhou, Cuncai
Abstract: Gallbladder cancer (GBC) is a relatively rare but fatal gastrointestinal tumor. The microRNA-33b (miR-33b), a member of miR-33 family, is reported to function as a tumor suppressor in various cancers. Notably, miR-33 was predicted to target CROCC based on microarray-based analysis. Hereby, we aimed to characterize the effect of miR-33b on epithelial–mesenchymal transition (EMT) in GBC and the potential mechanism involved with the regulation of CROCC. In GBC cell lines, miR-33b expressed at low levels, and CROCC expressed at high levels, with enhanced EMT process. To further examine the specific mechanism of miR-33b and CROCC in GBC, the GBC cells were treated with the miR-33b mimic/inhibitor or siRNA-CROCC to assess the expression alteration of EMT-related genes and cell proliferation, migration, and invasion. MiR-33b was verified to target and down-regulate the expression of CROCC. The miR-33b up-regulation or CROCC silencing was observed to increase the level of E-cadherin but decrease the levels of N-cadherin and Vimentin, corresponding to impeded cell proliferation, migration, invasion, EMT, and tumor growth. The findings suggest that miR-33b up-regulation hinders GBC development through down-regulating CROCC, which was achieved by inhibition of EMT. The present study may provide an insight on a novel target for GBC treatment.